A cross-sectional study on preferred employment settings of final-year nursing students in Israel - Yael Sela; Keren Grinberg; Yair Shapiro; Rachel Nissanholtz-Gannot (BMC, 2020)
Abstract Background Despite the growing demand for community nurses, their number remains relatively low. We examined perceptions of final-year nursing students regarding their preferred work setting after graduation and the factors affecting their choice. Methods A cross-sectional survey using a structured questionnaire was developed specifically for this study. The questionnaire was distributed among fourth-year students from all nursing training frameworks across Israel. Results Of 281 respondents (76.6% women, average age, 29.3 years), most (80.9%) preferred working in hospitals, while 5% preferred community settings; 14% were undecided. Students' knowledge on hospital nurses' tasks was greater compared to their knowledge on community nurses' tasks. Moreover, hospital nurses' tasks were perceived as more important than those of community nurses. The contribution of clinical placement in hospital nursing was perceived as significantly more meaningful than the contribution of clinical placement in community nursing. The vast majority of students (94.3%) stated that they would prefer to undergo a hospital nursing internship. A significant correlation was noted between students' clinical placement, the exposure to community nursing roles, and the perception of the community nurse's role: clinical placements that were perceived as a positive experience led to a more positive perception of community nurses' roles. Conclusions Nursing students' perception of community nursing is based upon limited information which does not reflect community nurses' actual role and work.